6t+3(2-5)=4-7t

Simple and best practice solution for 6t+3(2-5)=4-7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+3(2-5)=4-7t equation:


Simplifying
6t + 3(2 + -5) = 4 + -7t

Combine like terms: 2 + -5 = -3
6t + 3(-3) = 4 + -7t

Multiply 3 * -3
6t + -9 = 4 + -7t

Reorder the terms:
-9 + 6t = 4 + -7t

Solving
-9 + 6t = 4 + -7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '7t' to each side of the equation.
-9 + 6t + 7t = 4 + -7t + 7t

Combine like terms: 6t + 7t = 13t
-9 + 13t = 4 + -7t + 7t

Combine like terms: -7t + 7t = 0
-9 + 13t = 4 + 0
-9 + 13t = 4

Add '9' to each side of the equation.
-9 + 9 + 13t = 4 + 9

Combine like terms: -9 + 9 = 0
0 + 13t = 4 + 9
13t = 4 + 9

Combine like terms: 4 + 9 = 13
13t = 13

Divide each side by '13'.
t = 1

Simplifying
t = 1

See similar equations:

| 9-14x+5x^2=0 | | -5x-21=-8x+8 | | 6a^2-2ab-8b^2=0 | | -8x+6=30x-41 | | Log7(x^12/(x-3)) | | .3/4.5 | | 1/4+3/10= | | 8x-9y=-7 | | z^4+3i-4=0 | | 7x+10=4x-14 | | .05t+20=.07t+10 | | 5-(6m-6)=2m+5 | | 6x-3y=40 | | -26.5=8x-9x | | 5x+12=53 | | 5.4-(3-1/3)= | | 8-x=2x-16 | | .25x+1.25=-.67x+.83 | | 5.4-(3-1/3) | | 4.5x-3x=24.5 | | 50x+100=150 | | 20m+.05=10m+.07 | | 5.7x+.6=6.2x-3.4 | | .84-.09x=.3(.25x-1.6) | | 5/-2(w-1)=15 | | 10g-8g-2=14 | | -0.4=0.03x+0.15 | | 3(1x^2+5x-50)=0 | | xy+5x+5y=25 | | 54-11x=12+10x | | 4(x+4)=96 | | 54-11x=12+10k |

Equations solver categories